2015
DOI: 10.1073/pnas.1522401112
|View full text |Cite
|
Sign up to set email alerts
|

Mouse embryonic fibroblasts exhibit extensive developmental and phenotypic diversity

Abstract: Analysis of embryonic fibroblasts from GFP reporter mice indicates that the fibroblast cell type harbors a large collection of developmentally and phenotypically heterogeneous subtypes. Some of these cells exhibit multipotency, whereas others do not. Multiparameter flow cytometry analysis shows that a large number of distinct populations of fibroblast-like cells can be found in cultures initiated from different embryonic organs, and cells sorted according to their surface phenotype typically retain their chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…The cross talk between cancer cells, HSCs/PSCs/CAFs and other cells of the tumor microenvironment (TME) regulates the expression of cytokines and exosomes that promote desmoplasia, cancer cell proliferation and stemness, angiogenesis, inflammation/immunosuppression, invasion, and metastasis (Erez et al 2010; Kraman et al 2010; Chen et al 2014a; Haqq et al 2014; Ohlund et al 2014; Albrengues et al 2015). There is a large diversity in the origin, phenotype, and function of CAFs (Ohlund et al 2014; Ishii et al 2015; Singhal et al 2016). Recent studies have identified CAF subpopulations that promote tumor progression via multiple mechanisms and whose presence in tumors correlates with a poor outcome in cancer patients (Albrengues et al 2014; Haqq et al 2014; Scherz-Shouval et al 2014).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…The cross talk between cancer cells, HSCs/PSCs/CAFs and other cells of the tumor microenvironment (TME) regulates the expression of cytokines and exosomes that promote desmoplasia, cancer cell proliferation and stemness, angiogenesis, inflammation/immunosuppression, invasion, and metastasis (Erez et al 2010; Kraman et al 2010; Chen et al 2014a; Haqq et al 2014; Ohlund et al 2014; Albrengues et al 2015). There is a large diversity in the origin, phenotype, and function of CAFs (Ohlund et al 2014; Ishii et al 2015; Singhal et al 2016). Recent studies have identified CAF subpopulations that promote tumor progression via multiple mechanisms and whose presence in tumors correlates with a poor outcome in cancer patients (Albrengues et al 2014; Haqq et al 2014; Scherz-Shouval et al 2014).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…MEFs were isolated as previously described (59). Briefly, the embryos between E13 and E15 were minced and typsinized for 20 minutes, after the heads, tails, limbs, and most of the internal organs were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Because MEFs display extensive developmental and phenotypic heterogeneity (Singhal et al , 2016), we used adenovirus-5–mediated expression of Cre recombinase (Ad5-Cre) to ablate Actb and/or Actg1 in both primary and large T antigen immortalized MEFs controlled against the same MEFs infected with Ad5-GFP. α sm -Actin and ÎČ cyto -actin transcripts predominated in primary MEFs, whereas α sm -actin was most abundant at the protein level, with equivalent levels of ÎČ cyto - and Îł cyto -actin protein expressed despite their marked differences in transcript levels.…”
Section: Introductionmentioning
confidence: 99%